2024
DOI: 10.3389/fcimb.2024.1336773
|View full text |Cite
|
Sign up to set email alerts
|

Isobavachalcone exhibits antifungal and antibiofilm effects against C. albicans by disrupting cell wall/membrane integrity and inducing apoptosis and autophagy

Weidong Qian,
Jiaxing Lu,
Chang Gao
et al.

Abstract: Isobavachalcone (IBC) is a natural flavonoid with multiple pharmacological properties. This study aimed to evaluate the efficacy of IBC against planktonic growth and biofilms of Candida albicans (C. albicans) and the mechanisms underlying its antifungal action. The cell membrane integrity, cell metabolic viability, and cell morphology of C. albicans treated with IBC were evaluated using CLSM and FESEM analyses. Crystal violet staining, CLSM, and FESEM were used to assess the inhibition of biofilm formation, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…19 A recent study has demonstrated the antifungal properties of IBC against C. albicans. 23 However, the specific target proteins responsible for this activity remain unidentified. In the current investigation, we utilized DARTS and chemical genomics techniques to identify Eno1 as the target protein of IBC against C. albicans.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19 A recent study has demonstrated the antifungal properties of IBC against C. albicans. 23 However, the specific target proteins responsible for this activity remain unidentified. In the current investigation, we utilized DARTS and chemical genomics techniques to identify Eno1 as the target protein of IBC against C. albicans.…”
Section: ■ Discussionmentioning
confidence: 99%
“…A recent study has demonstrated the antifungal properties of IBC against C. albicans . However, the specific target proteins responsible for this activity remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 30 worms in M9 buffer with or without NBP at concentrations of 2, 10, 20, 50, 100, 200, and 400 µg/ml were placed in 96-well plates and incubated for 10 days at 25°C without agitation. The percentage of live worms was determined by the responses of the worms to LED light exposure for 20–30 s using an iRiS Digital Cell Imaging System after incubation ( Qian et al., 2024 ).…”
Section: Methodsmentioning
confidence: 99%